What influences a second generation's decision to join a family firm in China - Chen, Yihui (2011)
Family business plays an integral role in the development of Chinese economy. Similar to western counterparts, Chinese family firms are facing an urgent business succession issue. As the vital stakeholder in the family business succession, Chinese second generations remain seldom noticed by the academia. It is not clear that what factors influence the forming process of Chinese second generations’ determination to succeed their family firms or to pursue alternative careers and how it is impacted. This study is dedicated to explore and examine various factors that have influence on Chinese second generations’ decisions to enter their family firms or not. Firstly the definition of “family business” will be addressed followed by an illustration of the Chinese family business succession issue. Then, a literature review will be conducted to summarise past findings on this area and the methodology of this study will be justified. Finally, it will discuss main findings of this study and indicate their implications.